Incorporation of the microencapsulated antimicrobial agent phytoncide into denture base resin - Steve, An; Judge, Roy B; Wong, Rebecca H; Arzmi, Mohd Hafiz; Palamara, J E; Dashper, Stuart (Wiley Online Library, 2018)
Background This study aimed to fabricate a denture base resin (DBR) containing phytoncide microcapsules (PTMCs) and determine the mechanical properties of the resin and antifungal activity.